2011
DOI: 10.1016/j.jss.2010.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-Binding EGF-Like Growth Factor Promotes Intestinal Anastomotic Healing

Abstract: Background-We have accumulated multiple lines of evidence supporting the ability of HB-EGF to protect the intestines from injury and to augment the healing of partial-thickness scald burns of the skin. The aim of the current study was to investigate the role of heparin-binding EGFlike growth factor (HB-EGF) in intestinal anastomotic wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 46 publications
1
32
0
3
Order By: Relevance
“…These findings, in combination with our previous studies demonstrating that HB-EGF promotes intestinal restitution in vivo , 48, 49 support a potential future therapeutic role for HB-EGF in the promotion of cell migration and adhesion in processes such as wound healing and recovery from injury.…”
Section: Discussionsupporting
confidence: 80%
“…These findings, in combination with our previous studies demonstrating that HB-EGF promotes intestinal restitution in vivo , 48, 49 support a potential future therapeutic role for HB-EGF in the promotion of cell migration and adhesion in processes such as wound healing and recovery from injury.…”
Section: Discussionsupporting
confidence: 80%
“…However, isolated case reports continue to emerge that suggest heparin is able to promote tissue repair and inhibit inflammation in patients with burns (Ferreira Chacon et al, 2010). In animal models, application of heparin-binding epidermal growth factor-like growth factor (HB-EGF)-which is known to be upregulated both in human burn tissue and during healing of partial-thickness burn injuries specifically through potentiation of the expression of transforming growth factor-a, another member of the EGF family of growth factors involved in wound repair (Cribbs et al, 1998)-can promote healing of ileal tissue 120 after experimental reanastomosis surgery (Radulescu et al, 2011). Localization of HB-EGF through binding to HSPG facilitates juxtacrine inhibition of cell proliferation by this growth factor, and disruption of this binding allows the released HB-EGF to function as an autocrine mitogen (Prince et al, 2010).…”
Section: Would Healing and Tissue Repairmentioning
confidence: 99%
“…We also showed that HB-EGF knockout (KO) mice subjected to I/R injury have significantly impaired angiogenesis compared to their wild type (WT) counterparts [31]. Additionally, we used a model of intestinal anastomotic wound healing to show that HB-EGF transgenic (TG) mice have significantly increased angiogenesis and improved anastomotic healing compared to their WT counterparts [73]. In separate studies, we have examined the effects of HB-EGF on pericytes.…”
Section: Effects Of Hb-egf During Intestinal Injurymentioning
confidence: 99%
“…However, upon exposure to intestinal injury, HB-EGF TG mice have increased resistance to HS/R [36] and experimental NEC [25]. In addition, overexpression of HB-EGF in HB-EGF TG mice promoted intestinal anastomotic wound healing [73]. Conversely, we have examined the effects of HB-EGF loss-of-expression on recovery from intestinal injury, and have found that HB-EGF KO mice have increased susceptibility to HS/R [49] and experimental NEC [24].…”
Section: Effects Of Hb-egf During Intestinal Injurymentioning
confidence: 99%